THERMODYNAMIC PROPERTIES OF NATURAL LEPIDOLITE - Paukov I.E.; Kovalevskaya Yu.A.; Kiseleva I.A.; Shuriga T.N. (My University, 2007)
Lepidolite is a widespread iron-poor lithium–aluminum mica, the composition of which approaches the ideal formula KLi1.5Al1.5AlSi3O10F2. However, natural lepidolite has a much more complex variable composition owing to isovalent and heterovalent isomorphic substitutions resulting in the formation of isomorphic series with muscovite, biotite, phlogopite, siderophyllite, and various lithium micas. According to the recent mica nomenclature, lepidolite is a lithium mica of intermediate composition between trilithionite (KLi1.5Al1.5AlSi3O10F2) and polylithionite (KLi2AlSi4O10F2). Lepidolite is a characteristic mineral of rare-metal granites and pegmatites, occurs in metasomatic rocks and greisens, and is used as a lithium ore and as a source of rubidium and cesium, which can be recovered from it as by-products.
Keywords: lepidolite